Early diagnostic the grading stages of dengue haemorrhagic fever - Abdul Rahim, H. (Institute of Electrical and Electronics Engineers, 2009)
Single frequency bioelectrical impedance analysis (BIA) is an inexpensive, quick and painless means of estimating body composition. In this paper, BIA parameters employed for predicting hemoglobin (Hb) in dengue patients. The BIA technique passes a low-amplitude electrical current, in the range of 500µA to 800µA, at a single frequency of 50 kHz. BIA data was sampled from 210 (comprises of 119 males and 91 females) serologically confirmed dengue fever (DF) and dengue hemorrhagic fever (DHF) patients, hospitalized at the Hospital Universiti Kebangsaan Malaysia (HUKM). After applying multiple regression analysis, it was found out that risk, number of day, anorexia, blood tendency and ERBO were found to be significant independent determinants of predicting the grading stages on DHF.